2014
DOI: 10.1039/c4ra06070a
|View full text |Cite
|
Sign up to set email alerts
|

Nitridation effect of the α-Al2O3 substrates on the quality of the GaN films grown by pulsed laser deposition

Abstract: High-quality GaN films with sharp and abrupt interfaces have been achieved on nitrided α-Al2O3 substrates by pulsed laser deposition. The effect of nitridation on the properties and the growth mechanism of GaN films have been carefully studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
3
14
1
Order By: Relevance
“…On the one hand, these results confirm the single-crystalline hexagonal GaN films have been grown on Si(111) substrates 27 33 34 . On the other hand, an in-plane epitaxial relationship is determined to be GaN[11 0]//AlN[11 0]//Si[1 0] 19 31 32 , which is well consistent with the result of RHEED measurement. X-ray rocking curve (XRC) is a normal method to determine the crystalline quality of GaN films, because it is demonstrated that the full-width at half-maximum (FWHM) of GaN(0002) and GaN(10 2) XRC is related to the dislocation density in as-grown GaN films 2 32 .…”
supporting
confidence: 79%
See 1 more Smart Citation
“…On the one hand, these results confirm the single-crystalline hexagonal GaN films have been grown on Si(111) substrates 27 33 34 . On the other hand, an in-plane epitaxial relationship is determined to be GaN[11 0]//AlN[11 0]//Si[1 0] 19 31 32 , which is well consistent with the result of RHEED measurement. X-ray rocking curve (XRC) is a normal method to determine the crystalline quality of GaN films, because it is demonstrated that the full-width at half-maximum (FWHM) of GaN(0002) and GaN(10 2) XRC is related to the dislocation density in as-grown GaN films 2 32 .…”
supporting
confidence: 79%
“…When the growth temperature is too low, the GaN precursors can’t receive enough energy for the migration to their lowest energy crystal positions, which are superimposed by additional GaN precursors and eventually leads to the formation of large islands 30 . When the growth temperature is too high, the active AlN may react with high-energy Ga plasmas and lead to formation of AlGaN layer during the initial growth 31 32 33 34 . In this layer, there are many defects are formed, which is detrimental to the subsequent growth of GaN films, and eventually rough the GaN surfaces.…”
mentioning
confidence: 99%
“…These are much smaller than those in our previous work with FWHMs for GaN(0002) and GaN(10-12) of 231.2 and 253.1 arcsec, respectively22. The possible reason may be attributed to the effectively suppress the GaN/LSAT interfacial reactions24. Because we use lower RF plasma radical generator power of 500 W during the initial growth, the interfacial reactions between N plasmas produced by RF plasma radical generator and O atoms diffused from the substrates can be suppressed, and eventually results in the higher crystalline quality of GaN.…”
contrasting
confidence: 59%
“…Because we use lower RF plasma radical generator power of 500 W during the initial growth, the interfacial reactions between N plasmas produced by RF plasma radical generator and O atoms diffused from the substrates can be suppressed, and eventually results in the higher crystalline quality of GaN. Additionally, it is known that the FWHM of GaN(0002) is related to the skew dislocation that is formed by the various height of substrates, and the FWHM of GaN(10-12) is respected to the pure edge and mixed dislocations which are generated during the coalescence process among the mis-oriented individual islands242526. The skew dislocation density, and pure edge and mixed dislocation densities in as-grown GaN epi-layer are estimated to be 7.9 × 10 7 , and 8.8 × 10 7  cm −2 , respectively2728.…”
mentioning
confidence: 99%
“…Due to the limitation of GIXR measurement, the thickness of tested films is required to be within 100 nm, 34 thin AlN films are used for this analysis. [35][36][37] As shown in Figure 6(a), the typical GIXR measurement curve for $40 nm-thick AlN film and its theoretical curve are fitted by LEPTOS software on the basis of the Fresnel equation, 38,39 using the thickness of AlN epitaxial layer as a parameter.…”
Section: Resultsmentioning
confidence: 99%